A study on the factors contributing to the employee performance at Pejabat Tanah Dan Jajahan Tanah Merah / Che Redhana Che Fauzi - Che Fauzi, Che Redhana (2015)
This study aims to investigate the factors that can contribute to the employee performance at Pejabat Tanah dan Jajahan Tanah Merah. Based on the literature review, there are four factors are identified (training and development, physical work environment, rewards and recognition and leadership behaviour) that can affect the employee performance within the organization. Moreover, a total of 160 questionnaires were distributed to the employees that working in Pejabat Tanah dan Jajahan Tanah Merah and Pejabat Tanah dan Jajahan Machang by using simple random technique as sampling technique. However, only 130 questionnaires were filled and returned back to the researcher and the remaining were unreturned. The data solicited have been analyzed by using Statistical Package for Social Sciences (SPSS) version 16.0 in order to find out the actual result for this study. Based on the result obtained, there is a positive relationship between leadership behavior and employee performance in the organization. The finding indicates that the leadership behavior is significantly and positively related with employee performance. The study also revealed that there is no positive relationship between training and development, physical work environment, reward and recognition and employee performance in the organization. It means that, training and development, physical work environment as well as reward and recognition were not significantly related with the employee performance in the organization. Finally, the researcher was discussed about the findings and provides several recommendations derived from the findings.